Advances in the functions of CTRP6 in the development and progression of the malignancy - Hu, Bo; Qian, Xiaolan; Qian, Ping; Xu, Guangtao; Jin, Xin; Chen, Deqing; Xu, Long; Tang, Jie; Wu, Wenjing; Li, Wanlu; Zhang, Jin (Frontiers in Genetics, 2022)
CTRP6, a member of the C1q/TNF-related protein (CTRP) family, has gained increasing scientific interest because of its regulatory role in tumor progression. Previous studies have shown that CTRP6 is closely involved in regulating various pathophysiological processes, including glucose and lipid metabolism, cell proliferation, apoptosis, and inflammation. To date, CTRP6 has been identified as related to 8 different malignancies, including lung cancer, oral cancer, gastric cancer, colon cancer, liver cancer, bladder cancer, renal cancer, and ovarian cancer. CTRP6 is reported to be associated with tumor progression by activating a series of related signal networks. This review article mainly discusses the biochemistry and pleiotropic pathophysiological functions of CTRP6 as a new molecular mediator in carcinogenesis, hoping that the information summarized herein could make a modest contribution to the development of novel cancer treatments in the future.